A scoping review on how field epidemiology training programs are addressing regional and global health priorities - Koyie, Stephen Leshan; Muehlen, Marion; Dhand, Navneet; Perrocheau, Anne (Frontiers in Public Health, 2024)
IntroductionRecent global health events underscore the critical need to strengthen public health capacity worldwide, with epidemiologists playing a key role in disease management at the population level. The international community has recognized the importance of enhancing the public health workforce, including epidemiology capacity. This scoping review explores how Field Epidemiology Training Program (FETP) trainees and graduates have been engaged by their respective health ministries to address public health threats.MethodsA literature search was conducted in electronic databases (Web of Science, PubMed, and Google) using specific keywords such as “Epidemiologist,” “Field Epidemiologist,” and “Health workforce.” The search focused on English-language articles published between January 2012 and December 2021. Relevant articles were analyzed descriptively, and data on FETP engagement, impact within health ministries, and career paths were extracted.ResultsThe search yielded 30 studies from various regions globally. FETP graduates and trainees were actively engaged in national health priorities, including COVID-19 responses such as surveillance, rapid response teams, and case investigations. FETPs have significantly contributed by developing surveillance systems, investigating outbreaks, and responding to natural disasters. Many FETP graduates have assumed leadership roles in Ministries of Health, NGOs, and international organizations.ConclusionFETP graduates are integral to priority public health programs and have significantly strengthened public health systems worldwide. Their contributions highlight the importance of investing in the public health workforce, including field epidemiology training, to effectively detect and respond to emerging outbreaks. Further research is needed to assess the long-term impact of FETP graduates on public health.